Motivation and Professional Development of Faculty Respondents in Community Colleges: A Case Study in Eastern Nepal - Phuyal, Pradeep (Journal of Management, 2023)
This research article investigates the design of professional development programs for community college lecturers in Nepal that meet their needs and increase their motivation. Using Maslow’s Hierarchy of Needs and Herzberg’s Dual-Factor theory, the study aims to identify the hygiene factors and motivators that influence lecturer motivation to participate in professional development opportunities, assess their level of motivation, and provide recommendations for effective program design. The research objectives are to identify strategies for designing professional development programs that address both hygiene factors and motivators influencing lecturer motivation and to improve the quality of education. Data from 125 full-time and part-time faculty members from 15 community campuses in specific regions of Nepal were collected. The study provides valuable insights into the factors that impact the professional development and motivation of community college lecturers. By addressing their needs, institutions can create a positive learning environment and better meet the needs of a diverse student population. The article concludes that the study’s findings can inform policy decisions related to professional development opportunities for community college lecturers in Nepal and other similar contexts, providing a framework for designing and implementing effective professional development programs worldwide. The study has some limitations in sample size and representativeness, but it provides a starting point for further research in this area. Overall, this research article emphasizes the importance of addressing the needs of community college lecturers in Nepal and similar contexts to improve the quality of education and empower low-income individuals.